2019
DOI: 10.1186/s13046-019-1361-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of COX-2, mPGES-1 and CYP4A by isoliquiritigenin blocks the angiogenic Akt signaling in glioma through ceRNA effect of miR-194-5p and lncRNA NEAT1

Abstract: Background Arachidonic acid (AA) metabolic enzymes including cyclooxygenase-2 (COX-2), microsomal prostaglandin E synthase-1 (mPGES-1) and cytochrome P450 (CYP) 4A11 play important roles in glioma angiogenesis. Thus, there is an urgent need to identify the underlying mechanisms and develop strategies to overcome them. Methods A homology model of human CYP4A11 was constructed using SYBYL-X 2.0. Structure-based virtual screening against COX-2, mPGES-1 and CYP4A11was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 48 publications
(62 reference statements)
2
63
0
Order By: Relevance
“…It has also been reported that MALAT1 can be used as ceRNA of miR-199a to promote the expression of ZHX1 , which in turn can regulate the proliferation of GBM cells [ 34 ]. The ceRNA effect between NEAT1 and miR-194-5p is related to the angiogenesis of glioma [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that MALAT1 can be used as ceRNA of miR-199a to promote the expression of ZHX1 , which in turn can regulate the proliferation of GBM cells [ 34 ]. The ceRNA effect between NEAT1 and miR-194-5p is related to the angiogenesis of glioma [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the cytochrome P450 superfamily of enzyme, such gene has been generally reported to participate in neurovascular function in the brain (Bylund et al, 2002). As for its correlations with GBM, recently, two successive related publications (Wang et al, 2018(Wang et al, , 2019 confirmed that CYP4X1 contributes to the inhibition of glioma angiogenesis. Glioma vasculature is quite significant for the initiation and progression of such disease (Hardee and Zagzag, 2012).…”
Section: Optimal Genes Relevant To Gbmmentioning
confidence: 99%
“…FGF can promote the division and chemotaxis of vascular endothelial cells and can participate in the PI3K/AKT signaling pathway to inhibit apoptosis of endothelial cells. Targeted inhibition of COX-2 and FGF expression down-regulates VEGF, thereby slowing the process of angiogenesis [ 67 ]. COX2 can be metabolized into prostaglandin E2 (PGE2) [ 68 ].…”
Section: Immunoregulatory Factorsmentioning
confidence: 99%